A netnography approach on the daily local-guided shopping tour experiences of travellers: An unexplored facet of the sharing economy. (January 2023) - Atsız, Ozan; Seyitoğlu, Faruk
This research explores the travellers' experience of daily local-guided shopping tours offered in a sharing economy platform-Withlocals using a netnography approach. Reviews of travellers participating in daily local-guided shopping tours in different destinations were gathered, and their content was analysed. As a result, seven main components of experiences of daily-local guided shopping tours revealed: guide, shopping companion, learning, hedonic experience, memorable experience, local interaction, and shop characteristics. The study substantially contributes to the shopping experience and sharing economy literature by providing a deep understanding of travellers' shopping experiences in the local guided tours organised through sharing economy platforms.